Influence of Polyethylene Glycol and Methanol Additions on the Properties of Ball-Milled Cu4B4C Composite Powders - BIYIK, Serkan (International Journal of Computational and Experimental Science and Engineering, 2024)
This study investigated the effect of different process control agent (PCA) usage on mechanical alloying behavior of boron carbide (B4C) reinforced copper (Cu) based composite powder. For this purpose, elemental Cu and B4C powders were weighed and powder specimens were prepared with respect to appropriate mass ratios (96% Cu and 4% B4C). Two different PCA additives, namely polyethylene glycol (PEG) and methanol, were also used to prepare powder samples. The amount of PCA was kept constant at 5wt.% for both specimen. These prepared powder samples were then milled using a planetary type ball-mill. After specified milling periods, milling runs were interrupted and powder samples were extracted from the milling vials for further powder characterization including powder morphology using scanning electron microscopy (SEM) and average particle size (APS) via laser diffraction analysis (Mastersizer). Accordingly, after the completion of milling runs, namely 15 hours of ball-milling, methanol addition was found much more effective at reducing particle sizes than PEG. Final APS values for powder specimens having PEG and methanol as PCAs were determined to be 8.237 and 4.101 microns, respectively.